Itinerários da primeira previdência privada no Brasil: de uma iniciativa eclesial (1864) à consolidação de uma entidade aberta de previdência complementar, sem fins lucrativos (1993) - Oppermann, Everson (2014)
Itineraries of the First Private Pension Plan in Brazil, from an ecclesial initiative (1864) to the consolidation of an open entity for complementary pension funds (1993) is an interpretative historical narrative of the pension plan saga of an ecclesiastical institution of Lutheran confession originating with the German immigration in Brazil. As of 1864, German pastors sent to Brazil, having a pension plan culture, inspired in the associativism which gives foundation to mutualism, sought to resolve their problems of the lack of pension support in an environment in which their religion was only tolerated by the Brazilian Empire and in a context in which slavery still existed and where the official pension solutions were sponsored and granted only by the montepios (private social pension associations).Without any state financial or legal support, through a private and associative initiative, they discreetly founded, on March 1st of 1883, in Rio Grande do Sul, what the broader history should honor as the first private pension plan in Brazil. Characteristic of this organizational model and of the modern complementary pension plan, this was an organization of physical persons, with private capital and managed by the members themselves which aimed at paying a life time monthly income to invalid clergy, their widows and orphans, a true private pension plan. Throughout these 130 years of history the initiatives and the solutions were sometimes taken by the members themselves, sometimes by the Territorial Church of Prussia (Germany), the sponsorship of the models alternating between Brazil and Germany, due to the First and Second World Wars, until finally, as of 1952, and later 1974, it was possible for these religious people to join the official social security system in Brazil, and in the end they were able to consolidate the last open private pension plan non-profit entity, to be authorized to work in Brazil with the name of Luterprev, in 1993. This is the current stage of this pension plan historical process which presents itself as ciclical and evolutionary. This unique history of the private pension plan is representative not only in the area of the Evangelical Church of Lutheran Confession in Brazil, the theological confession of which has been present in the country since 1824, but is also significant in the midst of the broader history of private pension systems in Brazil, since it inaugurates, in an unprecedented way, the theme within the Brazilian ecclesiastical historiography, equally contributing, from the specific to the general, to the pension historiography in Brazil. From the administrative science point of view a discussion is proposed, which is applicable to various types of human organizations, about questioning axes related to the established historical phases such as ethicization , professionalization and (financial) capitalization as being a dialog between the theory of organizations and theology. From the historical perspective, this accomplishment should also be registered as a new contribution of the German immigration in the country when in 2014 190 years of this immigration to the country is commemorated.